Sickness, Hygienic Education and Village Practice: Tuberculosis in the Life of a Cobbler - Tuija Saarinen (Journal of Ethnology and Folkloristics)
The understanding of sickness and health depends on culture and age and is a part of our worldview. Sickness and health are thus in a central position in human life. Tuberculosis, for example, was formerly a common disease in Finland. Before the Second World War there did not exist medicines that cured people of tuberculosis. The first concord of antibiotics was received in 1947. Vaccinations against tuberculosis started on a mass scale in the following year. The article focuses on one person, who suffered from tuberculosis. He was a village cobbler called Juho Mäkäräinen (1892–1967). The study draws on a variety of sources including the villagers’ interviews, Juho Mäkäräinen’s autobiography and letters. All sources deal with the writers’, their relatives’ or neighbours’ health. Life in a village society was concentrated on health and its care. Very much attention was focused on hygienic education, as well. Because infectious diseases like tuberculosis were feared, most people tried to hide their disease in order not to be ostracised. Thus tuberculosis and its influence on the course of human life is a part of our common history of everyday life.